110 CHART ABSTRACTION BY RESIDENTS VERSUS TRAINED ABSTRACTORS. Issue 1 (1st January 2007) - Wall, T. C.; Benton, E. C.; Houston, T. K.
Abstract : Background: Chart audit is one method for evaluating resident performance, but audit using trained abstractors is limited by cost and feasibility. Purpose: Our objective was to compare agreement in performance of preventive services as measured by trained abstractors versus residents' self-abstraction of charts in a pediatrics continuity clinic. Methods: Patients who presented to continuity clinic for a well-child visit were identified from check-in sheets. Charts were audited by blinded, trained abstractors to assess resident performance on specific preventive services performance measures: assessment of eye alignment, car seat advice, smoke exposure screening, smoking cessation advice for parents, and immunization status. Residents ( n = 37) abstracted their charts (mean charts per resident = 8 [SD 1.9]) after being instructed on the data abstraction form. We assessed performance (percentage of appropriate patients receiving services) as measured by residents and abstractors. Results: Resident-measured performance was similar (within 5%) to that of the chart abstractor for four of the six measures. Measures that did not have prompts in the chart (eye alignment and smoking cessation advice) had the lowest agreement and highest disagreement in overall performance. Conclusions: Performance as measured by self-abstraction can be accomplished by residents if charts are designed for clear documentation. Resident-measured performance was lower than that measured by trained abstractor for eye alignment and smoking cessation advice.